Analytical investigation of the dynamic properties of passive engine mounting - Fazidah binti Saad (Kulliyyah of Engineering, International Islamic University Malaysia, 2011)
Engine mount is an automotive component that is essential in supporting the engine static state in order to prevent engine bounce from shock excitation and to isolate engine vibration caused by engine disturbances in the complete speed range. The main objective of this study is to analyze the dynamic properties which are the natural frequencies and modeshapes of different types of passive engine mounts. In this study, four passive (rubber) engine mount models were considered. The modal analysis were computed by using finite element software, ABAQUS and the results obtained were the modeshapes of the engine mounts. Modeshapes are the deflection shapes taken on by a system when excited at one of its natural frequencies. The corresponding modeshapes of all the rubber engine mount models were computed both in presence and absence of the engine's weight and the results are compared with the results from impact test which has been conducted to one of the engine mount. The computer simulated model of these mounts was analyzed and later the effect of the load applied on the engine mounts were compared with the engine mounts without the load. The results from the modal analysis demonstrated variety in the natural frequency values for all types of passive engine mounts. The modeshapes results showed the trend of bending mode, torsion mode and also the mixture of both. From the modehshapes results, the most deformed spot in the engine mounts can be identified. The results showed that the engine mounting with more metal contact will have the highest frequency of 987.56 Hz when analyzed without the engine weight while the engine mount with less metal contact will have the highest frequency of 1456.20 Hz when analyzed with the engine weight. This shows that rubber engine mounts with the least metal contact design had the highest frequency value of all and this signifies that it can provide the best damper for the engine weight. As a conclusion, the natural frequency of the passive engine mount depends strongly on the applied load although theoretically the natural frequency of a system should not be affected by the applied load. The variations happen because of the rubber viscoelastic nature. Besides that, the natural frequency of the rubber engine mounts also depend on their designs as the least metal contact design showed higher natural frequency value. The results of this study will open up a passage to researchers to study and improve the elastomeric engine mounts.